2009
DOI: 10.1103/physrevb.79.161306
|View full text |Cite
|
Sign up to set email alerts
|

Universality of bias- and temperature-induced dephasing in ballistic electronic interferometers

Abstract: We performed a transport measurement in a ballistic Aharonov-Bohm ring and a Fabry-Pérot-type interferometer. In both cases we found that the interference signal is reversed at a certain bias voltage and that the visibility decays exponentially as a function of temperature, being in a strong analogy with recent reports on the electronic Mach-Zehnder interferometers. By analyzing the data including those in the previous works, the energy scales that characterize the dephasing are found to be dominantly dependen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
5
12
0
Order By: Relevance
“…14,15 A number of experiments have measured the dephasing rate in ballistic quantum dots [16][17][18][19][20] and rings. [21][22][23][24] The dephasing rate is extracted from the temperature ͑T͒ dependence of the AB oscillation amplitude. For ballistic rings, it is found that the AB amplitude ⌬R AB decrease with T according to the relationship ⌬R AB ϰ exp͑− L / ͑T͒͒.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 A number of experiments have measured the dephasing rate in ballistic quantum dots [16][17][18][19][20] and rings. [21][22][23][24] The dephasing rate is extracted from the temperature ͑T͒ dependence of the AB oscillation amplitude. For ballistic rings, it is found that the AB amplitude ⌬R AB decrease with T according to the relationship ⌬R AB ϰ exp͑− L / ͑T͒͒.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Gaussian envelop of the visibility V / expðÀV 2 =2V 2 l Þ revealed in Ref. [11] and also observed in Fabry-Pérot interferometers [13] has not been accounted for. In Fig.…”
Section: T à1mentioning
confidence: 96%
“…However, these electronic versions of optical experiments suffer from one major problem: an electron carries a charge with which it interacts with the surrounding world, leading to a finite quantum coherence length and a finite energy exchange length. Recently, both lengths have been measured in the IQH regime at a filling factor 2, definitively showing the role of the interaction between the inner and outer edge state [2,3,10].While the dependence of the coherence length with temperature has been clearly identified to result from the thermal charge noise in the neighboring edge state [3], it has not yet been possible to clearly identify the role of energy exchanges on the repeatedly observed but poorly understood Gaussian shape of the visibility as a function of the bias voltage [11][12][13]. It has been demonstrated recently that the energy exchange between the edge states, which form at a filling factor 2, can be frozen by opening a gap in the excitations of the inner edge state (IES).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In open systems, i.e. when the conductance of the device σ is much larger than 2e 2 / h, electronic analogues of Mach-Zehnder [3][4][5] and Fabry-Pérot [6][7][8][9][10][11] interferometers have made it possible to study and control electron dephasing processes within ES and to estimate the electron phase coherence length [4,5,12]. In particular, McClure et al [7] used interference checkerboard patterns generated in a Fabry-Pérot geometry to determine the edge state velocity in the quantum Hall regime.…”
Section: Introductionmentioning
confidence: 99%